Effect of Different Water-Based and Gel-Based Conductive Media on the Efficacy of Electric Pulp Tester (Journal of Fatima Jinnah Medical University, 2024)
Background: The Electric Pulp Tester (EPT) is a valuable diagnostic tool used in dentistry to assess the vitality of dental pulp. However, the effectiveness of the EPT can be influenced by the type of conductive media used during the test. This study aimed to investigate the impact of different water-based and gel-based conductive media on the efficacy of EPT.Subjects and Methods: An Analytical observational study conducted at the School of Dentistry PIMS Islamabad. The Study period was six months from May to October 2022. Three different water-based and gel-based conductive media was applied on the 100 healthy maxillary central incisors to check the efficacy of EPT with different substances. The recorded data were analyzed through SPSS 21.0 for Windows.Results: The mean age of study participants was 22.5 ± 1.2. The ultrasound gel has the least pulpal sensory threshold 4.11 ± 1.26. Independent t-test was applied to find the correlation between gender and preference of materials. P value
Keywords: Electric pulp test; Dental pulp; Trauma; Dental Caries; Gel; Gender